Targeted Deletion of the USTA and UvSLT2 Genes Efficiently in Ustilaginoidea virens With the CRISPR-Cas9 System - Liang, Yafeng; Han, Yu; Wang, Chenfang; Jiang, Cong; Xu, Jin-Rong (Frontiers in Plant Science, 2018)
Ustilaginoidea virens is the causal agent of rice false smut, one of the major fungal diseases of rice. However, there are only limited molecular studies with this important pathogen due to the lack of efficient approaches for generating targeted gene disruption mutants. In this study, we used the CRISPR-Cas9 system to efficiently generate mutants deleted of the USTA ustiloxin and UvSLT2 MAP kinase genes. Three gRNA spacers of USTA, UA01, UA13, and UA21, were expressed with the RNAP III promoter of Gln-tRNA. For all of them, the homologous gene replacement frequency was higher when the Cas9 and gRNA constructs were transformed into U. virens on the same vector than sequentially. UA01, the spacer with the highest on-target score, had the highest knockout frequency of 90%, which was over 200 times higher than that of Agrobacterium tumefaciens-mediated transformation (ATMT) for generating ustA mutants. None of these USTA spacers had predicted off-targets with 1 or 2-nt variations. For predicted off-targets with 3 or 4-nt variations, mutations were not detected in 10 ustA mutants generated with spacer UA13 or UA21, indicating a relatively low frequency of off-target mutations in U. virens. For UvSLT2, the homologous gene replacement frequency was 50% with CRISPR-Cas9, which also was significantly higher than that of ATMT. Whereas ustA mutants had no detectable phenotypes, Uvslt2 mutants were slightly reduced in growth rate and reduced over 70% in conidiation. Deletion of UvSLT2 also increased sensitivity to cell wall stresses but tolerance to hyperosmotic or oxidative stresses. Taken together, our results showed that the CRISPR-Cas9 system can be used as an efficient gene replacement or editing approach in U. virens and the UvSlt2 MAP kinase pathway has a conserved role in cell wall integrity.